A giant tonsillolith - Anil Kumar Bhoweer (Wolters Kluwer Medknow Publications, 2008)
An extremely rare case of giant tonsillolith is presented here. Large tonsillolith are rare to be seen now and the cases reported in the literature are very few in number. When they appear on routine radiograph, they are usually labeled as non-specific calcifications or confused with other calcifying conditions. A possibility of tonsillar calcifications should be kept in mind since these tonsilloliths often cast shadows over the mandible in routine radiographs, especially lateral oblique view of the mandible and orthopantomograms. Etiology, clinical features, radiographic diagnosis and its confirmation are discussed in this presentation.